2022
DOI: 10.4314/ejst.v15i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater quality: Physicochemical and bacteriological evidence from boreholes in Sangayan Diriya village, northeast Nigeria

Abstract: The poor geology of Sangayan Diriya village has barred residents from getting access to water from the groundwater in their homes from time immemorial. This study was aimed at assessing the quality of boreholes sunk in close proximity to River Diriya wherein eight water samples were aseptically collected from the two available boreholes; borehole A (BA1, BA2, BA3 and BA4) and borehole B (BB1, BB2, BB3 and BB4). Standard procedures were employed for determining physicochemical properties, while pour plate metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In another instance, a communally-owned water facility, when its control is in a designated hand of one or more people, may not be distorted in quality easily. Adeleye 32 had suggested that powered or motorised well facility may be of better quality than the facility with manual mode of fetching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another instance, a communally-owned water facility, when its control is in a designated hand of one or more people, may not be distorted in quality easily. Adeleye 32 had suggested that powered or motorised well facility may be of better quality than the facility with manual mode of fetching.…”
Section: Resultsmentioning
confidence: 99%
“…Powered and/or motorised wells had been suggested to keep the well water in a good condition and sustainable water quality. 32 These accessories need to be kept in good and hygienic condition when not in use and should be adjudged free of filth and clean enough to be used at a point in time.…”
Section: Resultsmentioning
confidence: 99%